2011
DOI: 10.1002/j.2161-1939.2011.tb00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Entering Communities: Social Justice Oriented Disaster Response Counseling

Abstract: Cirecie west-olatunji and rachael D. goodman    Counselors need to learn how to effectively and respectfully enter into communities hit by disasters and create collaborative partnerships with community members. Using critical consciousness theory, the authors describe a humanistic, culturally responsive approach to disaster response counseling for marginalized individuals and communities and discuss empowering clients through culture-centered interventions and providing social justice advocacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Counselor educators’ focus on these concepts is typically designed to help either White students develop a greater awareness or trainees examine these constructs in society at large (Pieterse, ; Rothman et al, ). Unfortunately, there has been less attention to the multicultural and social justice inequities of marginalized students (e.g., students of color; lesbian, gay, bisexual, transgender, and queer [LGBTQ] students) within counselor education training programs (Barcus & Crowley, ; Dickson, Argus‐Calvo, & Tafoya, ; Gomez, Khurshid, Freitag, & Lachuk, ; Haizlip, ; Haskins et al, ; Hernández, Almeida, & Carranza, ; West‐Olatunji & Goodman, ). Furthermore, Barcus and Crowley () and Haskins et al () found that students of color feel isolated and ill prepared because of irrelevant course content or content that fails to include perspectives of marginalized practitioners.…”
mentioning
confidence: 99%
“…Counselor educators’ focus on these concepts is typically designed to help either White students develop a greater awareness or trainees examine these constructs in society at large (Pieterse, ; Rothman et al, ). Unfortunately, there has been less attention to the multicultural and social justice inequities of marginalized students (e.g., students of color; lesbian, gay, bisexual, transgender, and queer [LGBTQ] students) within counselor education training programs (Barcus & Crowley, ; Dickson, Argus‐Calvo, & Tafoya, ; Gomez, Khurshid, Freitag, & Lachuk, ; Haizlip, ; Haskins et al, ; Hernández, Almeida, & Carranza, ; West‐Olatunji & Goodman, ). Furthermore, Barcus and Crowley () and Haskins et al () found that students of color feel isolated and ill prepared because of irrelevant course content or content that fails to include perspectives of marginalized practitioners.…”
mentioning
confidence: 99%
“…The findings from our study revealed that the emotional experiences of community members were exacerbated by the "exploitation" they experienced from companies and professional organizations (i.e., rent inflation, insurance scams, and larger systemic issues related to the rebuilding of the community) West-Olatunji, & Goodman, 2011). Illuminating the existing op pressive structures already in Northern California, participants acknowledged that "social inequities against vulnerable communities" were more evident and pronounced in the aftermath of the fires.…”
Section: Collaborating With Local Communities To Fight Inequitiesmentioning
confidence: 73%
“…Doing so may allay certain fears and misperceptions, while concurrently laying the foundation for collaboration in the provision of disaster spiritual and emotional care services. For instance, clinicians can “engage in interactions with [clergy] and other professionals who work in targeted disaster areas to increase their understanding of culturally responsive approaches to mental health care that complement the mores, beliefs, values, and traditions of people in diverse communities” (West-Olatunji & Goodman, 2011, p. 179). Then clinicians can partner with clergy, serving disaster survivors’ mental health and R/S needs in ways that are more likely to be perceived as culturally sensitive and empowering (West-Olatunji & Goodman, 2011).…”
Section: Discussionmentioning
confidence: 99%